Using a Fully Expressive Avatar to Collaborate in Virtual Reality: Evaluation of Task Performance, Presence, and Attraction - Wu, Yuanjie; Wang, Yu; Jung, Sungchul; Hoermann, Simon; Lindeman, Robert W. (Frontiers in Virtual Reality, 2021)
Avatar-mediated collaboration in virtual environments is becoming more and more prevalent. However, current consumer systems are not suited to fully replicate real-world nonverbal communication. We present a novel avatar system for collaboration in virtual reality, which supports high levels of nonverbal expression by tracking behavior such as body movement, hand gesture, and facial expression. The system was built using camera tracking technology only. Therefore, in contrast to many other high-level tracking systems, it does not require users to wear additional trackers on their bodies. We compared our highly expressive system with a consumer setup extended with two body-worn trackers in a dyadic study. We investigated users’ performance, such as completion time and accuracy, as well as the presence and interpersonal attraction in a virtual charades game using an asymmetric control scheme. The results show that participants interacting with highly expressive avatars felt more social presence and attraction and exhibited better task performance than those interacting with partners represented using low-expressive avatars. Hence, we conclude that virtual reality avatar systems benefit from a higher level of nonverbal expressiveness, which can be achieved without additional body-worn trackers.